Adopción de un proceso contable como medio para la aplicación de las NIIF para PYMES en la empresa FELAINI S.A., periodo comprendido entre enero y diciembre del 2011 - Reyes Barzallo, Nancy Rocío (2013)
The integration of global markets has forced to seek harmonization of accounting financial reporting, these trends lead to the development of a set of global accounting standards, the International Financial Reporting Standards IFRS or IFRS for its acronym in English (International Financial Reporting Standards), therefore set a goal to adopt an accounting process as a means of implementing IFRS SMEs FELAINI Company S.A, period January to December 2011, being essential to use the deductive method allowing analysis records from the main to the sub accounts, likewise, to obtain the desired result, it was necessary to rely on the analytical method and the inductive method allowing to analyze the general to the particular and thus formulate conclusions. The proposed methodology for the implementation of this model did in three stages: planning, accounting and monitoring process, allowing to establish the following conclusions: The IFRS for SMEs provides that to make the relevant settings in the transition period is appropriate to create an account in equity, called transition effects, in this account will be charged all resulting values of the respective adjustments, the company does not have a policy governing the account Cash and cash equivalents, therefore remained investment for more than three months as a cash account, which by order of the IFRS for SMEs was moved to a temporary investment account; There is no policy governing the granting of loans to its customers nor has a collection plan for your portfolio, therefore when making reconciliation of Balance value was determined as uncollectible, and complying with the requirements of the IFRS for SMEs, which was detected within Receivables comprised a loan to one of partners, so we proceeded to reclassify the account receivables related parties, was found to have been acquired assets by the company but not used in the production or supply of goods or services or for administrative purposes, but maintained in lease rents for what was recorded as investments; The company has an accounting system, it had not been registered as active nor had made the respective amortization, so we proceeded to recognize as an asset intangible, the company obtained a lower yield compared to previous year falling their usefulness in a 34.77% compared to 2010, with total obligations maintaining firm represents half of what you own in assets, the assets of the company are financed by 46.40% with resources of its partners and the rest is financed by third parties, such as suppliers, financial institutions, etc. It concludes with the following conclusions: Managers must begin training staff involved in the management of accounting information for the adoption of IFRS for SMEs assured of obtaining financial statements free of errors, create policies which regulate the accounting activities because so far has been recording the transactions on the basis of Generally Accepted Accounting Principles; must make the corresponding commitment to accounting policies and its constant maintenance, use caution when applying the IFRS for SMEs as some of standards can become counter tax laws and can fall into breaches and comply with accounting requirements, tax and legal statement, as its failure leads to receive appropriate sanctions law.